Internet addiction: a new addiction? (Medical Journal of Indonesia, 2019)
The internet today has become an integral part of daily life that facilitates communication, education, and entertainment. The behavioral pattern of excessive internet usage has similarities to substance addiction, such as tolerance, withdrawal, repeated failure to reduce or quit, and impairment in daily life. Yet, there is no consistent physiological change that accompanies excessive use of the internet, as there is in excessive substance use. Neurological and neuroimaging studies of excessive internet users show biological changes in the prefrontal cortex that are similar to those found in other addictive syndromes. Brain structure changes also occur in the temporal cortex and ventral striatum, compromising executive function in planning and reasoning and increasing impulsive risk, resulting in loss of control over internet use. Of all the potential online applications known to cause addiction, only internet gaming disorder has been selected in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) as a condition for further study.